Reflexos das políticas públicas de inclusão social no perfil dos alunos ingressantes na UFC no período 2007-2014 - Correia, Maria de Jesus de Sá (2017)
This quantitative-qualitative study aims to analyze the reflection on the socioeconomic profile of the Federal University of Ceará’s (UFC) student due to the implementation of programs, projects and actions aimed at the restructuring and expansion of the institution and the democratization of access to undergraduate courses of this Institution of Higher Education (HEI). To do so, two periods of time were analysed: 2007 - 2010, in which the selection of students for undergraduate courses was conducted through the Vestibular Exam, and the period between the years 2011 and 2014, when the institution began to adopt the Exame Nacional do Ensino Médio, as a form of evaluation, and the Sistema de Seleção Unificado - SiSU, as a procedure for filling vacancies made available for admission. Based on authors including Lopes (2000), Andriola (2011), Barros (2015), the research interprets data made available in 8 editions of the UFC Statistical Yearbook. The results show that there was an increase of 26% in the number of new students on the institution, comparing the two periods. Comparing the profile of the students who entered in the university via the Vestibular Exam and via Enem/SiSu, it was observed that, amongst the participants via the Vestibular, men aged between 17 and 18, brown-skinned, from private schools, with family income of about 6.5 minimum wages were predominant. Amongst those that entered the university via the Enem/SiSU, before the quotas policy was adopted, men aged between 19 and 24, from private schools, with family income of about 5.7 minimum wages predominate. Amongst the entrants via Enem/Sisu, after quotas law was adopted, men aged between 19 and 24, with a family income of about 4.5 minimum wages predominate. Almost half of the new students (45%) attended public schools, 42% of them fully. It was concluded that the change in the selection process enabled an increase in the number of students from public schools, especially in Fortaleza’s and Sobral’s campi. In other campi, the change on the selection process and the adoption of Quotas Act did not cause significant changes in the access of students from public schools.